Applying the socio-ecological systems framework to assess the sustainability of tropical cattle ranching in Mexico - Figueroa, Daniela; Galicia, Leopoldo; Ávila Foucat, Véronique Sophie; Díaz-Morales, Benito (Frontiers in Sustainable Food Systems, 2025)
The conceptual framework of socio-ecological systems (SES) has been used to redirect resource management practices towards more sustainable scenarios. Utilizing surveys conducted with 350 producers of a silvopastoral cattle network in southern Mexico, the structure and interactions of cattle SES were characterized. Furthermore, based on information derived from a workshop with producers, the framework was operationalized through variables representing action situations and generating outcomes in terms of management, organizational issues, and ecosystem services. This participatory exercise allowed for the identification of locally relevant sustainability components and ranges that can be generalized to other similar SES in Latin America, specific socio-ecological challenges, and potential actions leading to maximizing the sustainability of silvopastoral ranches in the tropics. Challenges include an excessive number of intermediaries, labor conditions accentuating poverty, marketing chains inaccessible to small scale producers, and low diversification. These issues can be addressed within the cattle SES through technical and financial support from involved governmental institutions and strengthening the local governance system. This work bridges gaps in cattle research by highlighting that sustainable intensification through the establishment of silvopastoral systems is possible within specific ranges, and sustainability can be defined, understood, and built by producers from the territories.